Analýza mazacího systému motoru vozidla Formule Student - Liška, David (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2018)
Tato práce se zabývá analýzou použitého mazacího systému na osmé generaci vozidla Dragon 8 týmu TU Brno Racing. V úvodu práce objasňuje soutěž Formula Student, které se studentský tým účastní, jejími pravidly a omezeními ovlivňující mazací systém spalovacího motoru. Dále se práce zabývá možnostmi řešení olejového chlazení a rešerší používaných komponent v mazacím systému. Pro mazací systém je vypočítán teoretický objemový průtok a je následně ověřen při měření skutečného průtoku potřebného k určení chladícího výkonu olejového chladiče.

This thesis deals with the analysis of the used lubrication system on the eighth generation of Dragon 8 car from team TU Brno Racing. In the beginning of the thesis there is clarifying the Formula Student competition, in which the student team participates, explains its rules and limitations affecting the combustion engine lubrication system. Furthermore, the thesis deals with the possibilities of oil cooling systems and the search of the used components in lubrication system. For the lubrication system is calculated the theoretical volumetric flow rate by an oil pump and then it is verified by measuring the actual flow rate required to determine the cooling capacity of the oil cooler.
Formula Student Engine Oil System Function Analysis
Keywords: Mazací systém; Formula Student; olejový chladič; olejové čerpadlo; měření průtoků; výpočet chladícího výkonu olejového chladiče; Lubrication system; Formula Student; oil cooler; oil pump; flow measurement; calculation of cooling capacity of oil cooler